2020
DOI: 10.1177/1357633x19900459
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplant recipients’ experiences and perspectives of a telehealth-delivered lifestyle programme: A qualitative study

Abstract: Introduction Dietary modification and exercise are encouraged to address cardiometabolic risk factors after solid organ transplantation. However, the lived experience of attempting positive lifestyle changes for liver transplant recipients is not known. The aim of this study was to explore the experiences of liver transplant recipients and their perspectives of a 12-week telehealth lifestyle programme and assess the feasibility of this innovative health service. Methods Focus groups and one-on-one interviews w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Adopting a MedDiet outside of the Mediterranean region has its challenges, 30 - 33 but with appropriate support, we found the MedDiet was an acceptable strategy to improve diet quality in an Australian liver transplant population. 34 The acceptability of the MedDiet pattern in Western societies and to what degree of adherence to “traditional” MedDiet principles is necessary for clinical effect is an ongoing scientific debate. 35 Nonetheless, with increasing clinical interest in shifting dietetic services to facilitate more cardioprotective diet patterns in liver clinics, 36 considerations of multicultural patient groups are a welcome development to better translate the evidence for MedDiet effectiveness for those living outside of the Mediterranean.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adopting a MedDiet outside of the Mediterranean region has its challenges, 30 - 33 but with appropriate support, we found the MedDiet was an acceptable strategy to improve diet quality in an Australian liver transplant population. 34 The acceptability of the MedDiet pattern in Western societies and to what degree of adherence to “traditional” MedDiet principles is necessary for clinical effect is an ongoing scientific debate. 35 Nonetheless, with increasing clinical interest in shifting dietetic services to facilitate more cardioprotective diet patterns in liver clinics, 36 considerations of multicultural patient groups are a welcome development to better translate the evidence for MedDiet effectiveness for those living outside of the Mediterranean.…”
Section: Discussionmentioning
confidence: 99%
“… 56 In addition, qualitative analysis from participants indicated that the cost savings to patients through reduced travel time and lost work hours associated with face-to-face appointments were highly valued. 34 Experience with rapid disruptions to telehealth delivery of care during the COVID-19 pandemic 57 is likely to drive demand for this transition for many services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important aspect is the willingness of patients to implement apps or eHealth solutions into their lives, independent of the usability, whereby the general acceptance for medical adherence apps is high [31,52,55]. The integration of social backing systems such as friends and family as well as patient priorities (daily schedule, sports, work) is important to support adherence to an app [62]. The use of a self‐managing app can improve the systolic blood pressure over time only by better self‐awareness [45].…”
Section: Mobile Applications (Apps)mentioning
confidence: 99%
“…Transplant centers have a large catchment area resulting in long travel distances for patients. Therefore, telemedicine concepts with web‐based platforms [40,41], mobile smartphone apps [29,44,61,64], videoconferencing [43,62,65,66], chat [42,61,67], remote vital sign monitoring [32,38,48,61], or various of those combinations [68,69] are well suited for transplantation follow‐up. However, the added benefit of new telemedicine concepts compared to standard care after transplantation must be demonstrated in order to justify the use of additional costs.…”
Section: Mobile Applications (Apps)mentioning
confidence: 99%